A rare case of complicated pericardial effusion with Elizabethkingia meningoseptica from Iran - Sedigh Ebrahim-Saraie, Hadi; Heidari, Hamid; Khashei, Reza; Nabavizadeh, Seyed Hesamedin (Cellular and Molecular Biology, 2018)
Infections due to Elizabethkingia meningoseptica, a Gram-negative oxidative bacterium are frequently founded in neonatal and immunocompromised individuals. The notable characteristic of this organism is its multi-drug resistance to common antibiotics used for infections caused by Gram-negative bacteria. We report a rare case of complicated pericardial effusion due to E. meningoseptica in a 2-year-old boy, who was admitted with chief complaints of fever and tachypnea (mentioned by his parents) and suffered from a rare lung malignancy (lymphangioleiomyomatosis). He was successfully treated with vancomycin. E. meningoseptica infection is a rare situation in immunocompetent hosts, and we concluded that this infection was probably originated from device medicine or even hands of healthcare workers.